A novel concept for a fully digital particle detector. (1st April 2022) - Casse, G.; Massari, N.; Franks, M.; Parmesan, L.
Abstract: Silicon sensors are the most diffuse position sensitive device in particle physics experiments and in countless applications in science and technology. They had a spectacular progress in performance over almost 40 years since their first introduction, but their evolution is now slowing down. The position resolution for single particle hits is larger than a few microns in the most advanced sensors. This value was reached already over 30 years ago [1]. The minimum ionising path length a sensor can detect is several tens of microns. There are fundamental reasons why these limits will not be substantially improved by further refinements of the current technology. This makes silicon sensors unsuitable to applications where the physics signature is the short path of a recoiling atom and constrains the layout of physics experiments where they represent by far the best option like high energy physics collider experiments. In perspective, the availability of sensors with sub-micron spatial resolution, in the order of a few tens of nanometres, would be a disruptive change for the sensor technology with a foreseeable huge impact on experiment layout and various applications of these devices. For providing such a leap in resolution, we propose a novel design based on a purely digital circuit. This disruptive concept potentially enables pixel sizes much smaller than 1 μm 2 and a number of advantages in terms of power consumption, readout speed and reduced thickness (for low mass sensors).